Why and how of technology integration for services in university libraries? (2017)
University libraries are expected to provide efficient services to users and this can be facilitated with technology. The technology to be adopted must be such that will benefit both the librarians and the users. For technology to be adopted in a university library, adequate planning must be taken to ensure that the most relevant technology is adopted that will improve the services provided. The planning should include the consideration of factors such as type of technology, perceived usefulness, perceived ease of use, cost and Information and Communication Technology (ICT) skills of librarians. The study investigated the type of technology integrated and factors considered in planning in ten university libraries in South-west, Nigeria using an interview schedule to collect data from a librarian in charge of technology in each of the universities. Results were thematically analysed. Findings revealed that all the university libraries were using software, social media but only four libraries were using Radio Frequency Identification. Perceived usefulness and perceived ease of use were factors considered for technology integration. University libraries have integrated technology for various activities but sustainability of these technologies should be ensured and regular trainings to improve the ICT skills of the library personnel should be done.